Foreigners Everywhere : Venice Biennale - Khalili, Bouchra (2024)
Contribution to the international exhibition of the 60th Venice Biennale with the mixed media installation "The Mapping Journey Project", the works on paper "The Constellations Series", and the textile "Sea-Drifts".